Diastolic mechanisms of impaired exercise tolerance in aortic valve disease. - Oldershaw, P J (1983)
In order to determine the significance of abnormalities of diastolic function in patients with left ventricular hypertrophy, exercise echocardiography to heart rates of 140 to 150 beats/min was performed in 18 normal subjects and 14 patients after aortic valve replacement. Simultaneous echo-, phono-, and electrocardiograms were recorded. Left ventricular cavity size was determined at end-diastole and end-systole. The timing of mitral valve opening and closure was measured, and hence left ventricular filling time derived, expressed either as ms/beat, or s/min when multiplied by heart rate. Isovolumic relaxation was taken as the interval between A2 and mitral valve opening. Systolic function, assessed from cavity dimensions, peak VCF, and QA2 interval was normal in all but two patients at rest and on exercise. Isovolumic relaxation was prolonged at rest in the patients to 85 +/- 8 ms (normal 69 +/- 9 ms), but left ventricular filling times were normal. With exercise, in normal subjects, isovolumic relaxation remained constant, but filling times dropped strikingly from 380 +/- 66 ms/beat, or 27 +/- 2 s/min at rest to 115 +/- 10 ms/beat or 16 +/- 2 s/min. In patients with left ventricular hypertrophy, isovolumic relaxation dropped on exercise to 41 +/- 15 ms. Filling periods were normal at rest, 367 +/- 67 ms/beat or 27 +/- 3 s/min, but failed to show the normal drop with exercise, being 240 +/- 44 ms/beat or 28 +/- 4 s/min. At heart rates above 120/min, separation between the two groups was complete. Thus, striking abnormalities of left ventricular filling can be demonstrated on exercise in patients with left ventricular hypertrophy. They appear to represent loss of mechanisms whereby rapid diastolic filling is achieved in the normal subject.